Efektivitas Relokasi Pasar Baru ke Pasar Puan Ramah di Kilometer Tujuh Kota Tanjungpinang Tahun 2022 - Eti Afrila; Nazaki Nazaki; Ryan Anggria Pratama (Social Issues Quarterly, 2023)
The market is a place where buying and selling transactions are carried out by more than one seller and buyer. Tanjungpinang City has the biggest market, namely Pasar Baru which is revitalized. The new market was revitalized to repair damaged stalls and as a better arrangement for the city of Tanjungpinang so that the new market would be more modern. The research method used in this research is descriptive qualitative method with 12 informants. Research Using data collection techniques in the form of observation, documentation and interviews. The research results show that the effectiveness of relocating a new market to the Puan Friendly market by the Pemko of Tanjungpinang through the Tanjungpinang City Regional Office and BUMD that the market relocation in Tanjungpinang has not been effective in achieving the program has not been successful in the market relocation objective. In the indicators of Program Objectives where the facilities and infrastructure provided by the government are still lacking, the Indicator of Response Speed ​​of Officers complaints of traders is not responded to by the Pemko, the Indicator of Monitoring Level there are still traders who lose goods, safety scales in the market are not guaranteed and Indicators of the level of income of traders in the market for friendly ladies has dropped dramatically and there have been losses.